2019
DOI: 10.1002/ddr.21539
|View full text |Cite
|
Sign up to set email alerts
|

Further modifications of 1H‐pyrrolo[2,3‐b]pyridine derivatives as inhibitors of human neutrophil elastase

Abstract: Human neutrophil elastase (HNE) is a potent protease that plays an important physiological role in many processes and is considered to be a multifunctional enzyme.HNE is also involved in a variety of pathologies affecting the respiratory system. Thus, compounds able to inhibit HNE proteolytic activity could represent effective therapeutics. We present here a new series of pyrrolo[2,3-b]pyridine derivatives of our previously reported potent HNE inhibitors. Our results show that position 2 of the pyrrolo[2,3-b]p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Sivelestat, a known HNE inhibitor, was used as a positive control. The inhibition assay was performed, as described previously [ 29 ]. Briefly, a solution containing 200 mM Tris-HCl (pH 7.5), 0.01% bovine serum albumin, 0.05% Tween-20, and 20 mU/mL of human neutrophil elastase was added to black, flat-bottom 96-well microtiter plates containing different concentrations of test compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Sivelestat, a known HNE inhibitor, was used as a positive control. The inhibition assay was performed, as described previously [ 29 ]. Briefly, a solution containing 200 mM Tris-HCl (pH 7.5), 0.01% bovine serum albumin, 0.05% Tween-20, and 20 mU/mL of human neutrophil elastase was added to black, flat-bottom 96-well microtiter plates containing different concentrations of test compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Starting from Scheme 1 , fragment 2 was inserted at the N-1 position of four different bi-heterocycles that were previously investigated by our research group as N(1)-CO- aryl(alkyl) derivatives: indoles (Crocetti et al, 2016 ), indazoles (Crocetti et al, 2011 , 2013 ), 7-azaindoles (Crocetti et al, 2018 ; Giovannoni et al, 2019 ) and 7-azaindazoles (data not shown). Indole derivatives 3a-c were obtained starting from the precursors 1a-c ( 1a : Shahidul et al, 2006 ; 1b : DeGraw and Goodman, 1964 ; 1c : Yuen et al, 2013 ) by treatment with 4-(chlorosulfonyl)phenyl pivalate 2 and sodium hydride in anhydrous tetrahydrofuran (THF) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Starting from Scheme 1, fragment 2 was inserted at the N-1 position of four different bi-heterocycles that were previously investigated by our research group as N(1)-CO-aryl(alkyl) derivatives: indoles (Crocetti et al, 2016), indazoles (Crocetti et al, 2011(Crocetti et al, , 2013, 7-azaindoles (Crocetti et al, 2018;Giovannoni et al, 2019) and 7-azaindazoles (data not shown). Indole SCHEME 3 | a Reagents and conditions.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, only two HNE inhibitors are commercially available: Sivelestat (Elaspol® 100), which is in use for the treatment of ALI and ARDS only marketed in Korea and Japan (Iwata et al, ), and Prolastin (purified α1‐AT), which is use for the treatment of α1‐antitrypsin deficiency (Bayer Corporation, ). In order to develop new compounds that modulate the HNE proteolytic activity, our research group has investigated several molecular scaffolds, such as indazoles (Crocetti et al, , ), indoles (Crocetti et al, ), azaindoles (Crocetti et al, ; Giovannoni et al, ), cinnolinones (Giovannoni et al, ), and thiazolones (Crocetti et al, ). Most recently, we focused on the synthesis isoxazol‐5(2 H )‐one derivatives (Giovannoni et al, ; Vergelli et al, ).…”
Section: Introductionmentioning
confidence: 99%